Evaluation of hybrid self-assembled liquid crystal systems for potential application in solar thermoelectric generator / Shahrir Razey Sahamir - Shahrir Razey , Sahamir (2018)
This research is motivated by the need to develop materials for a conceptual solar thermoelectric generator (STEG) device. Investigation on the key material parameters for STEG i.e. electrical conductivity, Seebeck coefficient and thermal conductivity was conducted. Liquid Crystal (LC) was chosen as the candidate material due to its capability for self-assembly. This work explores the two classes of LC materials with self-assembly: (1) a hybrid mixture of Polymer Electrolyte Liquid Crystal (PELC) system consisting of polyvinyl alcohol polymer (PVA), potassium iodide (KI) salt and nematic liquid crystal 4-Cyano-4'-pentylbiphenyl (5CB); and (2) a doped Discotic Liquid Crystals (DLCs) system consisting of 2,3,6,7,10,11-hexakis(hexyloxy)triphenylene (HAT6) and aluminium trichloride (AlCl3) salt. Tuneable thermoelectric properties of PELC were achieved with addition of different concentrations of 5CB into PVA polymer-KI electrolyte mixtures in PELC studies. It was found that the self-assembly of thermotropic LCs during transition increases the electrical conductivity and Seebeck coefficient performance in PELC system, whilst increased concentration of 5CB has reduced their thermal conductivity. In DLC studies, the HAT6 DLC which possesses a quasi-one-dimensional (1D) transport property was investigated for its electrical conductivity and optical properties in order to evaluate its potential as the active material component in STEG. The stacking of columnar discs of DLCs was found to favour its electrical conductivity as the behaviour similar to conduction in 1D nanowires was observed. The study of the structural of HAT6 and its effect on the electronic and thermal properties is investigated through Raman spectral analysis, and correlated to density functional theory (DFT) simulation. The results from Raman study indicates a high core to core correlation in the LC columnar phase, which has a ‘memory’ like effect that extends into isotropic phase at femtosecond timescale, which is supported by the electrical conductivity measurement of DLCs, in which the electrical conductivity is enhanced in the DLC phase. DFT simulation was also carried out in order to elucidate the basic properties of HAT6 such as the band gap. An interesting outcome of this simulation is that in a freely unspecified boundary model, when used to describe the core to core stacking, results in a more flexible HAT6 molecule with a reduced band gap. Thus, this work provides an understanding of relationship between columnar order and electrical conductivity of HAT6 molecule, and potential strategy for design of DLCs in electronic applications, specifically towards development of STEGs.